Insight into boron-doped diamond Raman spectra characteristic features. (May 2017) - Mortet, V.; Vlčková Živcová, Z.; Taylor, A.; Frank, O.; Hubík, P.; Trémouilles, D.; Jomard, F.; Barjon, J.; Kavan, L.
Abstract: Characteristic Raman features of boron-doped diamond layers with metallic conduction are studied experimentally and discussed in comparison with an extensive selection of literature data. Despite evidence that the main Raman bands are mostly characteristic features of carbon atom vibration modes, their position is found to be proportional to boron concentration. While the origin of the Raman bands located at c.a. 500 cm −1 remains unclear, the band centred at c.a. 1200 cm −1 is attributed to a maximum of phonon density of states due to softening of the Raman wave vector conservation rule. The downshift and broadening of the diamond line are attributed, primarily, to the domain size effect caused by scattering on boron impurities, secondly to the Fano effect due to electronic Raman interaction, and finally to lattice expansion due to the boron doping. Graphical abstract: